Bioorganometallic Compounds as Novel Drug Targets against Schistosomiasis in Sub-Saharan Africa: An alternative to Praziquantel? - Cuma Cumisa Ndamse; Priscilla Masamba; Abidemi Paul Kappo (Tabriz University of Medical Sciences, 2022)
Human schistosomiasis is a disease that mostly plagues the destitute of various tropical and sub-tropical countries, particularly in sub-Saharan Africa (SSA) and South America. It has significant effects on various health and economic-related matters. Globally, the burden of schistosomiasis has been controlled with a single chemotherapeutic drug, praziquantel (PZQ), which has recently demonstrated several clinical issues, including its inability to destroy juvenile schistosome worms and drug resistance because of its extensive use. The use of organometallic moieties in biological and medicinal chemistry has developed greatly and has led to their use in various anti-cancer and anti-infectious agents. The abundance of a range of organometallic compounds that can cause damage to the parasite has received tremendous feedback, with many already at clinical trials. The distinct redox biology of the schistosome parasite is a vulnerable element to the survival of the worm and has steered attempts toward the use of redox-directed bioorganometallic compounds. Disruption of the schistosome redox homeostasis through organometallic ions provides a novel drug target that could be used in overcoming the drawbacks of the mainstream drug and one that could possibly bypass the emergence of drug resistance.